2017
DOI: 10.1002/poc.3793
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer and electron localization as the origin of the anomeric effect in theOCOsegment of dimethoxymethane and spiroketals

Abstract: Every day, more evidence accumulates, leading to the conclusion that the stereoelectronic model through the nO → σ*C─O interaction is of minor relevance or even inoperative to explain conformational preference in the specific O─C─O segment. In the present study, dimethoxymethane (DMM) and some model spiroketals were chosen to develop a reliable and easy to apply methodology that is simple to interpret by experimental chemists. The general conformation observed in these molecules, present in many biologically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
1
6
0
Order By: Relevance
“…6 Then there is greater nO/nO steric hindrance in the equatorial conformer, which has parallel 2p-type nO filled orbitals again favouring the axial conformer (Figure 1c). 7,8,9,10 Finally and most recently, non-classical hydrogen bonds (NCHBs) such as transannular CHax•••OC interactions have been proposed by Nishio 11 and supported by Wiberg 12 and Cuevas 13 which introduce a further electrostatic factor. NCHBs occur when an electronegative atom (in this case O) interacts with a covalently bound X-H hydrogen but where the X atom is of moderate to low electronegativity (in this case C).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Then there is greater nO/nO steric hindrance in the equatorial conformer, which has parallel 2p-type nO filled orbitals again favouring the axial conformer (Figure 1c). 7,8,9,10 Finally and most recently, non-classical hydrogen bonds (NCHBs) such as transannular CHax•••OC interactions have been proposed by Nishio 11 and supported by Wiberg 12 and Cuevas 13 which introduce a further electrostatic factor. NCHBs occur when an electronegative atom (in this case O) interacts with a covalently bound X-H hydrogen but where the X atom is of moderate to low electronegativity (in this case C).…”
Section: Introductionmentioning
confidence: 99%
“…NCHBs occur when an electronegative atom (in this case O) interacts with a covalently bound X-H hydrogen but where the X atom is of moderate to low electronegativity (in this case C). 14,15 These authors [11][12][13] and particularly Wiberg 12 have argued an increasing significance for electrostatic interactions in determining the anomeric effect with a decreasing emphasis on the more widely propagated hyperconjugation model. It is the NCHB interactions which form the focus of this work, where we deconvolute [using Natural Bond Orbital (NBO) analysis, 16 Quantum Theory of Atoms in Molecules (QTAIM) 17 and Non Covalent Interactions (NCI) 18 ] their contributions relative to hyperconjugation, and provide quantitative support to this revision, in an approach which extends from a deeper analysis of our recent observations of 'pseudo' anomeric effects in cyclohexanes 2, 4, 5 and 8.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the same authors used the ED index to explain the conformational preference of dimethoxy‐methane and spiroketals . In these cases, they analyzed the atomic and molecular energetic components, as well as localization (Equation ) and delocalization indexes (Equation ), and their bonded ( Δ b ) and nonbonded ( Δ nb ) electronic contributions .…”
Section: Applications Of Qtaimmentioning
confidence: 99%
“…Adapted from New J Chem 2014;38:58925904 with permission of the Royal Society of Chemistry [46] Recently, the same authors used the ED index to explain the conformational preference of dimethoxy-methane and spiroketals. [50] In these cases, they analyzed the atomic and molecular energetic components, as well as localization (Equation (10)) and delocalization indexes (Equation (11)), and their bonded (Δ b ) and nonbonded (Δ nb ) electronic contributions. 1 It was observed that ED between electronegative atoms or total delocalization between nonbonded atoms is not the major contributor to the axial conformational preference observed in spiroketals that could be expected from hyperconjugative models.…”
Section: Conformational Analysis Of Small Moleculesmentioning
confidence: 99%
“…Electronic delocalization index DI(A,B), an average number of electrons delocalized between atoms A and B, is an additional information that can be extracted from AIM calculations. 43 Table 5 shows the delocalization index between the oxygen and the analyzed hydrogens. These values are higher when the hydrogen is closer to the carbonyl group, showing that the difference in chemical shifts of protons proR and proS may be attributed to this interaction.…”
Section: Computational Analysismentioning
confidence: 99%